Elemen Visual Desain Sampul Piringan Hitam Album Keroncong Produksi Lokananta Tahun 1959-1971 - Astina Astina Yuliana; Ana Rosmiati (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Vinyl records have various cover designs according to the development of modern technology. This study discusses the use of visualization of the album cover design of the 1959-1971 Lokananta keroncong album which is contained in several visual elements, namely typography, illustrations, colors and layouts. Based on the analysis conducted, the use of visual elements complement each other by having their own characteristics. Photographic and computer techniques were used on the album cover.